The Opinion of İstanbul University Faculty of Letters Department of Information and Record Management About Appointing the Graduates of Information and Record Management As Technical Staff In Accordance With State Personel Law no 657 Article 36/ II on Te - İstanbul Üniversitesi Edebiyat Fakültesi BBY Bölümü (Türk Kütüphaneciliği)
Technical services category reasons of librarians in Turkey are shared by İstanbul University Faculty of Letters Department of Information and Records Management in the professional discussion list kutup-l as an academic comment for some barriers recently.